Configuración jurídica de la asistencia religiosa en hospitales en Alemania, Italia y Portugal - Salido, Mercedes (Agencia Estatal Boletín Oficial del Estado, 2024)
The purpose of this paper is to analyze the legal regime of religious assistance in the health field in three different countries: Germany, Italy and Portugal. After a brief exposition of the treatment of the religious phenomenon in each territory, attention is given to the organization and limits of the exercise of religious assistance. It is verified, in the three States analyzed, the recognition of the right in favor of patients and the guarantee of access to hospital centers for religious ministers, upon request; however, although they coincide in terms of its foundation –the right to religious freedom–, they differ in their organization and the range of regulations in which it is collected
Legal configuration of religious assistance in hospitals in Germany, Italy and Portugal
Keywords: configuración juridica; asistencia religiosa; Alemania; Italia; Portugal; religious assistance; religious freedom; hospital; secularism